2009
DOI: 10.1158/1535-7163.mct-09-0243
|View full text |Cite
|
Sign up to set email alerts
|

Drug ratio–dependent antitumor activity of irinotecan and cisplatin combinations in vitro and in vivo

Abstract: Irinotecan and cisplatin are two established anticancer drugs, which together constitute an effective combination for treating small-cell lung cancer. We investigated whether the efficacy of this combination could be improved by controlling drug ratios following in vivo administration. Irinotecan and cisplatin combinations were evaluated systematically for drug ratio-dependent synergy in vitro using a panel of 20 tumor cell lines. In vitro screening informatics on drug ratio-dependent cytotoxicity identified a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 39 publications
2
66
0
Order By: Relevance
“…As different ratios of drug combinations may create different effects (synergistic, additive, or antagonistic), fixing ratios to achieve the best cytotoxicity effect and greatest synergy makes sense. 20 However, the traditional combination drug delivery system, namely the drug cocktail, is limited by the inconsistent biodistribution and pharmacokinetics of drugs and is extremely challenging for treatment optimization. 21 In order to solve these issues, the present study explored a new approach by covalently conjugating the two drugs at different molar ratios on a macromolecule through hydrolyzable linkers.…”
Section: Introductionmentioning
confidence: 99%
“…As different ratios of drug combinations may create different effects (synergistic, additive, or antagonistic), fixing ratios to achieve the best cytotoxicity effect and greatest synergy makes sense. 20 However, the traditional combination drug delivery system, namely the drug cocktail, is limited by the inconsistent biodistribution and pharmacokinetics of drugs and is extremely challenging for treatment optimization. 21 In order to solve these issues, the present study explored a new approach by covalently conjugating the two drugs at different molar ratios on a macromolecule through hydrolyzable linkers.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of drug resistance by multiple myeloma cells often requires that a combination of two or more drugs be prescribed to effectively promote cell death by synergistically disrupting different cellular mechanisms necessary for growth and survival (1). Although two drugs can demonstrate synergy, they are usually only synergistic, or exhibit the greatest synergy, at specific drug-to-drug molar ratios (2)(3)(4). Although the two drugs may be administered at the optimal drug ratio for synergy, this does not ensure that this ratio will be maintained at the tumor site due to differences in injection schedules, pharmacokinetic properties, metabolism, and nonuniform biodistribution (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…As described in the following section, results from multiple clinical trials have demonstrated that the CombiPlex platform is able to translate the identification of a synergistic drug ratio in a preclinical setting to the development of combination regimens with improved clinical efficacy [4,[21][22][23].…”
Section: Improving Combination Therapy Development Processesmentioning
confidence: 99%